Assessment Of Selected Physico-Chemical Parameters Of Groundwater In Chuka Igambang’ombe Constituency, Kenya - Maweu, Bonface K.; Chabari, Kithaka Samson; Nguku, James Kyalo (Machakos University Press, 2021)
Groundwater is an essential source of water for drinking and other domestic uses. Recently, there has been high dependence on groundwater due to water shortage as a result of changing climates, and higher costs of accessing piped water. An occurrence of the physico-chemical parameters of the groundwater in levels past the WHO highest permissible limits can cause serious health implications to the consumers of the groundwater. This study therefore, assessed the extent of the physico-chemical parameters concentration of the groundwater in Chuka, Igambang’ombe constituency. A total of five samples was collected from 5 boreholes in the Mucw’a and Ndagani regions surrounding the Chuka University main campus. Selected physical parameters were recorded onsite by use of portable apparatus. Samples for testing chemical parameters were collected and transported in cooler boxes to Chuka University laboratories for analysis. Physical parameters determined onsite were dissolved oxygen (DO), temperature, and the pH. Dissolved Oxygen meter, mercury thermometer, and pH meter were the equipment used to test the respective physical parameters. UV- spectrophotometry was used to analyze the chemical parameters: nitrates, and phosphates, where absorbance was recorded at a wavelength of 220-820 nm and 880nm respectively. The assessment was conducted during the relatively dry months of January to March. The temperature of the water ranged from 22.8-25.20C. The pH levels ranged from 4.50 – 9.50. The high altitude nitrate levels were 2.4mg/L, and 7.37mg/L at the low altitude. The phosphate concentrations were below detectable limits. The results were then compared with WHO standards for the highest permissible levels for the tested parameters to determine the suitability of the water for consumption. All the tested parameters lied within the WHO permissible limits for drinking water except for the pH levels.
Keywords: Groundwater; Physical parameters; Chemical parameters; Infiltration; Suitability; Chuka